Provision of Marketing Services in the Field of Digital Economy - Musayeva Shoira Azimovna,; Fayziev Sardorkhon Sanjarkhonovich. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article is devoted to identifying the role and improving the quality of marketing in the digital economy as a result of researches on difital transformation. And also offers are presented that can help improve the quality of sevices provided in all sectors of the economy.